Auxiliary Substrates for Elimination of Trichloroethene, Monochlorobenzene, and Benzene in a Sequential Anaerobic–Aerobic GAC Biobarrier - M Gozan; A Mueller; A Tiehm (ASEAN Journal of Chemical Engineering, 2007)
Sequential anaerobic-aerobic barrier is a novel concept for groundwater bioremediation. Trichloroethene (TCE), monochlorobenzene (MCB), and benzene (BZ) were used as model contaminants representing contaminant cocktails frequently found in the contaminated subsurface. The autochthonous microflora from a contaminated field was inoculated to eliminate model contaminants in a set of sequential anaerobic–aerobic granulated activated carbon (GAC) columns and batch studies. In the anaerobic column, the TCE was reductively dechlorinated through cis-dichloroethene (cis-DCE), vinyl chloride (VC), and ethene (ETH). Ethanol and sucrose as auxiliary substrates were added to donate electrons. In the second stage, MCB, BZ, and the lower chlorinated metabolites of TCE degradation, i.e. cis-Dichloroethene (cisDCE) and vinyl chloride (VC), were oxidatively degraded with addition of hydrogen peroxide and nitrate. This paper examines the influence of auxiliary substrates on the biological degradation of model pollutants. In the anaerobic barrier, the auxiliary substrates supply should be maintained low but stoichiometrically adequate for supporting reductive dechlorination. Supplying higher amount of auxiliary substrates provoked competitive reactions in anaerobic conditions, such as sulfate reduction and methanogenesis. If the auxiliary substrates are not utilized completely in the anaerobic phase, the remaining compounds flow into the aerobic phase. This led to unwanted conditions, i.e. oxidation of auxiliary substrates instead of pollutant elimination, and a higher consumption of electron acceptors. In the aerobic barrier, in particular, ethene proved to be a suitable auxiliary substrate for cometabolic degradation of cisDCE.